The Influence of Competence and Work Facilities on Employee Performance with Work Motivation as An Intervening Variable (Study at The Airnav Indonesia Branch Office in Merauke) - Hidayat, Galih Daniar; Christian, Ferdinandus; Astini, Rina (PT FORMOSA CENDEKIA GLOBAL, 2024)
The performance of Airnav Indonesia Office Branch Merauke, which has the task of providing flight navigation services in the South Papua region, is still less than optimal, as seen from the inconsistency in sending aircraft movement data every month.The purpose of the research conducted was to analyze the effect of competence, work facilitation on employee performance with work motivation as an intervening variable at the Airnav Indonesia Merauke Office. This research is quantitative research and uses a questionnaire as a research instrument. The sample for this research is the entire population, namely 50 employees at the Airnav Indonesia office Branch Merauke. Descriptive analysis test is used to analyze data by utilizing the help of SEM PLS software. The results of this study indicate that there is a significant influence between competence and performance, there is no significant influence between facilities and performance, and there is a significant influence between motivation and performance, there is a significant influence on competence on work motivation, there is a significant influence on facilities on motivation, there is a significant influence on competence on performance through work motivation, there is an influence related to work facilities on performance through work motivation, competence is the most dominant factor that has an influence on employee performance at the Airnav Indonesia Office in Merauke.